A Study On The Effect Of Zinc Oxide Nanoparticles In Staphylococcus Aureus - VANI C,; SERGIN G K,; ANNAMALAI A, (International Journal of Pharma and Bio Sciences, 2011)
Research concerning the impact of inorganic nanoparticles on cellular health will enable new developments in nanobiotechnology to reach their fullest potential. An improved understanding of nanoparticles and biological cell interactions can lead to the development of new sensing, diagnostic, and treatment capabilities, such as improved targeted drug delivery, gene therapy, magnetic resonance imaging (MRI) contrast agents, and biological warfare agent detection etc. The objective of the present study is to observe the growth-inhibitory effect of Zinc Oxide nanoparticles on the micro organism, Staphylococcus aureus. S. aureus is a gram positive micro organism and is consistently one of the four causes of nosocomial infections. Antibacterial activity, study of growth curve, protein estimation and SDS PAGE analysis were performed on S. aureus treated with different concentrations of 20, 40, 60, 80 and 100 µg/mL of ZnO nanoparticles. These studies have shown positive results for the antibacterial activity of ZnO nanoparticles against S. aureus and an indication that there occurs an optimal concentration for the application of ZnO nanoparticles which shows maximum antibacterial activity. Thus, it is useful to understand the nanopartices and its interaction with the microorganisms and its application in treatment. The results obtained from the protein estimation reveal that the proteins are important biological molecules that are fundamental to the proper functioning of cells and the organism and the nanoparticles bring about changes in the protein composition and levels.